Critical analysis of academic psychological discourse on terrorism - Alina Bezlaj (Psihološka Obzorja)
The following article contains a critical analysis of nine psychology articles published in the journal American Psychologist, which examine the topic of terrorism from different angles. In these articles, the authors discuss the process of radicalization through cognitive opening, with possible causes of becoming a terrorist including emotions, social identity and mental health problems. Through analysing these discourses, it will be argued that the a priori goal of such mechanistic models and theories of terrorism is the delegitimization of the political phenomenon, thereby implicitly or openly reflecting the ideological standpoint of their authors.